Narrative Analysis of Aboriginal Knowledge as A Tool for Learners’ Socialisation: Implications for Best Child-upbringing Practices in Cameroon - (:unkn) unknown (My University, 2025)
Aboriginal (Indigenous) knowledge systems are culture specific; they form the basis for a people’s livelihood. Folklore and Children’s traditional songs and games are one aspect of Indigenous knowledge systems. Through the songs and games children got to know their environment and acquired life skills among other things. This article dwells on the existence and performance of traditional children’s songs and games and the use of proverbs and folktales among children. Traditional children’s songs and games are no longer as popular as they used to be. In fact, it is possible that they are facing extinction. This paper also establishes that this status quo is as a result of quite a number of factors for example formal education and technological advancement among several others. Therefore, educationists and other key players are called upon to consider coming up with frame works which help advance Indigenous knowledge. Africa has always been an important source of rich information for knowledge production. The paper was anchored on the Eco-Cultural (ontogenesis) Theory of Bame Nsamenang (2015). Nsamenang (2015) explains the eco-cultural theories of development in what is known as social ontogenesis. The study created a theoretical stance known as social ontogenesis, which is grounded on an eco-cultural viewpoint and an indigenous West African idea. Curiosity about Africa has always existed, catering to many interests and imaginations. However, how can we educate and learn about Africa in a way that is influenced by an understanding of the rich cultural knowledge, complexity, and historical struggle of indigenous peoples to forge their own paths and aspirations? One could argue that understanding socialization and education techniques provides some crucial guidance in this quest for indigenous knowledge and epistemology. To educate young people, traditional African education has made use of a range of teaching and pedagogical techniques in addition
Keywords: African Research